Macroeconomic dynamics and the Phillips curve under diverse assumptions on the wage adjustment mechanism - Rodríguez Arana, Alejandro (Estudios Económicos de El Colegio de México, 2004)
In a quite simplified model, when nominal wages are completely predetermined, different macroeconomic shocks produce oscillations in output and inflation that can be stable or explosive. If they are stable, in many cases a peculiar dynamics, perhaps complex, appears, where output and inflation show cycles of multiple order. Even in those cases the cycles show well defined patterns. The model of this work suggests that in more real contexts marginal changes in certain rules of price adjustment could generate hyper sensibility of macroeconomic variables to some parameters, as well as dynamic instability.